Decision-making preceding induced abortion: a qualitative study of women's experiences in Kisumu, Kenya - Ulrika Rehnström Loi; Matilda Lindgren; Elisabeth Faxelid; Monica Oguttu; Marie Klingberg-Allvin (BMC, 2018)
Abstract Background Unwanted pregnancies and unsafe abortions are prevalent in regions where women and adolescent girls have unmet contraceptive needs. Globally, about 25 million unsafe abortions take place every year. In countries with restrictive abortion laws, safe abortion care is not always accessible. In Kenya, the high unwanted pregnancy rate resulting in unsafe abortions is a serious public health issue. Gaps exist in knowledge regarding women's decision-making processes in relation to induced abortions in Kenya. Decision-making is a fundamental factor for consideration when planning and implementing contraceptive services. This study explored decision-making processes preceding induced abortion among women with unwanted pregnancy in Kisumu, Kenya. Methods Individual face-to-face in-depth interviews were conducted with nine women aged 19-32 years old. Women who had experienced induced abortion were recruited after receiving post-abortion care at the Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH) or Kisumu East District Hospital (KDH) in Kisumu, Kenya. In total, 15 in-depth interviews using open-ended questions were conducted. All interviews were tape-recorded, transcribed and coded manually using inductive content analysis. Results Respondents described their own experiences regarding decision-making preceding induced abortion. This study shows that the main reasons for induced abortion were socio-economic stress and a lack of support from the male partner. In addition, deviance from family expectations and gender-based norms highly influenced the decision to have an abortion among the interviewed women. The principal decision maker was often the male partner who pressed for the termination of the pregnancy indirectly by declining his financial or social responsibilities or directly by demanding termination. In some cases, the male partner controlled decision-making by arranging an unsafe abortion without the woman's consent. Strategic choices regarding whom to confide in were employed as protection against abortion stigma. This contributed to a culture of silence around abortion and unwanted pregnancy, a factor that made women more vulnerable to complications. Conclusions The findings suggest that financial, social and gender-based dependencies influence women's agency and perceived options in decision-making regarding abortion.